KESANTUNAN BERBAHASA DALAM FILM "SANG PRAWIRA": KAJIAN PRAGMATIK - Marini, Marini; Simanjuntak, Hotma; Heryana, Nanang (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
Language politeness is an important key in communication, ensuring language is in accordance with norms and culture to maintain harmonious social relations. Language politeness not only applies in everyday life, but also has an important role in producing a film, one of which is the film Sang Prawira. This research focuses on analyzing politeness in the film Sang Prawira, directed by Ponti Gea. The choice of this film was based on an interest in the use of inappropriate language in several scenes. This research aims to find out and understand how language politeness is reflected in the speech of the characters in the film Sang Prawira, both compliance and violation of language politeness as well as the implementation of Indonesian language learning in Senior High Schools (SMA). The method used in this research is descriptive qualitative. The data collection technique used is a documentary study technique. The data analysis techniques used in this research are data reduction, data interpretation, data presentation, and drawing conclusions. The results of this research show that the film Sang Prawira includes the six maxims stated by Leech, both compliance and violation of language politeness and maintaining Asmah Haji Omar facial expressions as well as implementation of Indonesian language learning in drama texts in Senior High School (SMA) class XI semester. complete the 2013 curriculum.